The Development of an Adventure Game to Enhance English Vocabulary Learning - วรรณยศ, กาญจนา; เติมผล, สันติ; ปอสูงเนิน, สมภาร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to: 1) develop an interactive adventure game to promote English vocabulary learning, and 2) enhance learners’ basic English vocabulary knowledge through a game-based learning process. The sample group consisted of 20 Grade 4 students. The research instruments included a specially designed adventure game titled "Adventure in the English Vocabulary Land" and a satisfaction questionnaire to evaluate learners' perceptions of the game. The statistical methods used for data analysis were mean and standard deviation. The research findings revealed that learners expressed a high level of satisfaction with the game, with an average score of 4.31. This indicates that the developed game was effective in promoting basic English vocabulary learning and served as an engaging educational tool that stimulated learners' interest.